2018
DOI: 10.1177/0218492318757042
|View full text |Cite
|
Sign up to set email alerts
|

Pierre-Marie-Bamberger syndrome and solitary fibrous tumor: a rare association

Abstract: A solitary fibrous tumor originates in the pleura with variable degrees of invasion. Hypertrophic osteoarthropathy, known as Pierre-Marie-Bamberger syndrome, is characterized by clubbing of the fingers due to bone surface and soft tissue calcification, historically known as a bronchogenic carcinoma paraneoplastic syndrome; however, a few cases have been associated with solitary fibrous tumors. We describe the case of a 38-year-old woman who presented with clubbing of the fingers. Studies revealed an intrathora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…DPS occurs when a large SFT ectopically excretes Insulin-like growth factor 2 (IGF-2), resulting in a type of hyperinsulinemic hypoglycemia [6]. DPS was first exclusively described in 1930 by Doege and Potter as a non-islet cell tumor hypoglycemia [7].…”
Section: Introductionmentioning
confidence: 99%
“…DPS occurs when a large SFT ectopically excretes Insulin-like growth factor 2 (IGF-2), resulting in a type of hyperinsulinemic hypoglycemia [6]. DPS was first exclusively described in 1930 by Doege and Potter as a non-islet cell tumor hypoglycemia [7].…”
Section: Introductionmentioning
confidence: 99%
“…In large series of cases, the prevalence of lung neoplasm in patients with hypertrophic osteoarthropathy varied between 4% and 32%. [8] In a study that enrolled 81 patients with bronchopulmonary malignant tumors from our country, the authors found that 31.6% of the patients had a complete or incomplete Pierre Marie–Bamberger syndrome. [9] It is considered that the prevalence is higher in patients with nonsmall-cell lung tumors than in those with small-cell lung carcinoma probably due to a longer survival and a better prognosis of the former.…”
Section: Discussionmentioning
confidence: 99%
“…Larger tumours are more likely to present with symptoms, like cough, dyspnoea, pleuritic chest pain and haemoptysis due to compression of a bronchus [1]. SFTP may be associated with secondary hypertrophic osteoarthropathy also known as Pierre-Marie-Bamberger syndrome, characterized by digital clubbing, periostitis and arthritis, which is thought to be related to increased production of hyaluronic acid by tumour cells [1,3]. Although it is most commonly associated with non-small cell lung cancer, specifically adenocarcinoma (reported in 0.7-17%), a percentage of up to 20% of SFTP present with this paraneoplastic syndrome [4].…”
Section: Discussionmentioning
confidence: 99%
“…Resection of giant-sized tumours, such as the one described herein, can be more challenging, due to poor exposure and visualisation, as well as significant blood supply to the tumour [1,2]. Treatment of secondary hypertrophic osteoarthropathy is best achieved by definitive treatment of the primary pathology, whenever possible [3,4].…”
Section: Discussionmentioning
confidence: 99%